Gender-Based discrimination in hiring process: An example of Turkish employment agency - Kartal, Nur Banu (My University, 2019)
In 2019, women are still hindered and get discriminated in working life. Problems encountered by women in working life are; participation gap, the wage gap, horizontal gender segregation in vocational and sectoral distribution, vertical gap, the wealth and property gap, motherhood gap, unpaid domestic labor and care services, the feminization of labor. In line with that fact, the indicators show that in Turkey, women participate 38.3% less to the labor force, they are 36,5% less employed and yet, 3.8% more in unemployment with 12,6% of unemployment rate in comparison with men (TÜİK, 2018). The inadequate representation of women in employment is a universal issue, but when comparing Turkey with OECD countries, women's representation is far behind than the OECD average which brings a huge potential loss to the economy. At this point, one needs to ask this critical question: What constitutes gender-based discrimination that prevents women to have equal opportunities in working life? This study investigates gender discrimination in the hiring process based on the Turkish Employment Agency’s annual data. The gender discrimination is analyzed through public institutions, integrated with a comprehensive data of education levels and age compared to the more general studies

2019'da kadınlar çalışma hayatında hala engellenmekte ve ayrımcılığa uğramaktadır. Kadınların çalışma hayatında karşılaştıkları başlıca sorunlar; iş gücüne katılım açığı, ücret eşitsizliği, mesleki ve sektörel dağılımda yatay cinsiyet ayrışması, dikey cinsiyet ayrışması, servet ve mülkiyetteki eşitsizlik, annelik ayrımcılığı, ücretsiz ev içi emek ve bakım hizmetleri, emeğin feminizasyonudur. Göstergeler, Türkiye'de, kadınların erkeklerle karşılaştırıldığında, iş gücüne %38,3 daha az katıldığını, %36,5 daha az istihdam edildiğini ve buna rağmen %12,6 işsizlik oranıyla erkeklerden %3,8 daha fazla işsizlikte olduğunu göstermektedir (TÜİK, 2018). Kadınların istihdamda yetersiz temsili evrensel bir sorundur, ancak Türkiye OECD ülkeleriyle karşılaştırıldığında, kadınların iş hayatındaki temsili OECD ortalamasının çok gerisindedir, bu durum potansiyelin kullanılamadığını gösterir. Bu noktada şu soruyu sormak önemlidir : Kadınların çalışma hayatında eşit fırsatlara sahip olmasını önleyen cinsiyete dayalı ayrımcılık nedir? Yapılan bu çalışma, Türkiye İş Kurumu'nun (İŞKUR) yıllık verilerine dayanan, işe alım sürecindeki cinsiyet ayrımcılığını incelemektedir. İş hayatındaki cinsiyete dayalı ayrımcılık, kamu kurumları doğrultusunda analiz edilmekte, daha genel çalışmalara kıyasla, eğitim düzeyi ve yaşın da bulunduğu kapsamlı bir veri seti ile bütünleştirilmektedir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Gender-based discrimination; The wage gap; Labor economics; Cinsiyete dayalı ayrımcılık; Ücret eşitsizliği; Çalışma ekonomisi